Tradisi Makan Berhadap Adat Melayu Deli dalam Perspektif Al Qur'an - Aulia, Shila Dara; Arrahmah, Sayla; Safitri, Kayza (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The Deli Malays are a group of Malays originating from North Sumatra. The majority of people from the Deli Malay tribe are located in Deli Serdang, which is around Medan Madya City. The history of eating rice face to face was originally because life in the past among the Malay people was very Islamic, marrying off their children by means of arranged marriages and introducing families through the tradition of eating rice face to face. The purpose of this research is to know the tradition of eating against Deli Malay customs in the perspective of the Koran. Eating facing is a meal together or a meal with a plate. This type of research uses descriptive qualitative research by examining in depth about eating face to face or what is commonly called rice face to face. The results of the study found patterns of communication by using the interview method with one of the researchers' friends. Eating rice face to face is one of the traditional Malay processions that is highly awaited by the bride and groom in the wedding process. Eating rice face to face is not just for carrying out traditional processions, but has many symbolic meanings taken from this customary process. The results of the research are that it is permissible to use the tradition of eating with one's face as long as it does not violate religious rules in accordance with Islamic law. Keywords: Face Food, Deli Malay Customs, Al-Qur'an Perspective.